2013
DOI: 10.1016/j.ajpath.2013.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Inhibitor of NF-κB Translocation Ameliorates Experimental Atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of the arterial wall. NF-κB is a major regulator of inflammation that controls the expression of many genes involved in atherogenesis. Activated NF-κB was detected in human atherosclerotic plaques, and modulation of NF-κB inflammatory activity limits disease progression in mice. Herein, we investigate the anti-inflammatory and atheroprotective effects of a cell-permeable peptide containing the NF-κB nuclear localization sequence (NLS). In vascular smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 44 publications
(59 reference statements)
1
49
1
1
Order By: Relevance
“…Ranganathan and colleagues [105] used the selective nuclear export inhibitor KPT-sine (Karyopharm Therapeutics) in preclinical studies of acute myeloid leukemia. In line with this, Mallavia and colleagues [106] applied a specific peptide to inhibit nuclear import of NFκB in a model of experimental atherosclerosis. It might be well worth considering that the modulation of nuclear translocation of HIFs could provide therapeutic applicability to tumors.…”
Section: Discussionmentioning
confidence: 87%
“…Ranganathan and colleagues [105] used the selective nuclear export inhibitor KPT-sine (Karyopharm Therapeutics) in preclinical studies of acute myeloid leukemia. In line with this, Mallavia and colleagues [106] applied a specific peptide to inhibit nuclear import of NFκB in a model of experimental atherosclerosis. It might be well worth considering that the modulation of nuclear translocation of HIFs could provide therapeutic applicability to tumors.…”
Section: Discussionmentioning
confidence: 87%
“…Dysregulated NF-kB and STAT pathways contribute to diabetic nephropathy and atherosclerosis by inducing the transcription of many genes associated with inflammation, renal fibrosis (45)(46)(47), and the proatherogenic state (23,48). We have previously tested a number of potential novel approaches (e.g., kinase inhibitors, permeable peptides, and gene therapy) to tackle diabetic nephropathy and atherosclerosis by separately inhibiting the STAT and NF-kB pathways (23,26,28,29). Here, we demonstrated that DMAG treatment resulted in combined inhibition of the NF-kB and STAT pathways and subsequent downregulation of their inducible genes (e.g., cytokines, chemokines, and extracellular matrix proteins) both in diabetic mice and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Positive staining was expressed as percentage of total plaque area or number of positive cells per lesion area (26,27). Activated NF-kB in kidney and aorta was detected by Southwestern histochemistry using digoxigenin-labeled probes (26,28 (23). Murine monocyte/macrophage cell line (RAW 264.7, TIB-71; ATCC) was maintained in DMEM with 10% FBS.…”
Section: Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel sections were analyzed for collagen content (picrosirius red staining) and immunoperoxidase detection of T lymphocytes (CD4, BD Biosciences), macrophages (Moma2, Serotec, Oxford, UK), and monocyte chemoattractant protein-1 (CCL2, Santa Cruz Biotechnology, Santa Cruz, CA) as described [22]. STAT phosphorylation (P-STAT1, Santa Cruz Biotechnology; P-STAT3, Cell Signaling, Danvers, MA) and macrophage phenotypes (M1, arginase (Arg) II; M2, ArgI; Santa Cruz Biotechnology) were analyzed by immunofluorescence using Alexa Fluor 568 and 488 secondary antibodies (Invitrogen, Carlsbad, CA) followed by nuclear counterstain (4 0 ,6-diamidino-2-phenylindole) [18,22]. Appropriate antibodies were used as isotype controls.…”
Section: Atherosclerotic Lesion Analysismentioning
confidence: 99%